Efeito da aquisição do ecoico sobre a emergência de tatos expandidos - Freire, Marcela Ferreira da Silva Teixeira (Universidade Federal de São Carlos, 2024)
This work presents applied research conducted with three children with formal diagnosis with Autism Spectrum Disorder (ASD) aged 3, 4, and 9 years old. The aim was to test the effect of echoic expansion training on expanded tact responses in children with autism. Expansion was defined as an increase in the number of elements of tact and echoic responses. The hypothesis tested was whether expanded tact would emerge following expanded echoic instruction, which, if confirmed, could lead to a learning leap through stimulus control transfer, facilitating teaching processes of tact expansion and representing a teaching economy. A multiple probes design was used in the studies. A baseline protocol containing interspersed echoic, listener, and tact tasks was applied, followed by extended echoic teaching and subsequent testing. Only the results of the study on one of the participants give some support to the research hypothesis, in which the participant has shown some tact expansion without formal directed instruction.
Effect of the aquisition of echoic on the emergence of expanded tacts
Keywords: Ecoico expandido; Ensino de ecoico; Tato expandido; Comportamento emergente; Expanded echoic; Echoic instruction; Expanded tact; Emergent behavior; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL